A high-barrier and highly corrosion-resistant composite coating and its preparation method and application

By ultrasonic treatment of MXene powder and tannic acid in a solvent, the directional arrangement of MXene nanosheets is achieved, and mixed with polymer resin for spraying. This solves the problem of MXene nanosheets being easily degraded and difficult to be oriented in a humid environment, which is significant. Improved corrosion resistance of composite coatings.

CN118772740BActive Publication Date: 2025-01-24SHANDONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410929946.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2025-01-24
Estimated Expiration
2044-07-11

AI Technical Summary

Technical Problem

The existing MXene nanosheets are prone to degradation in humid environments and are difficult to achieve directional arrangement in polymer matrix, resulting in insufficient corrosion resistance of the composite coating.

Method used

By processing MXENE powder and tannic acid in the solvent, the load and directional discharge of the MXENE nanosometer is achieved, and the polymer resin is mixed with the surface of the metal substrate.

Benefits of technology

The directional parallel arrangement of MXene nanosheets is achieved to prevent accumulation and oxidative degradation, significantly improve the long-term corrosion resistance of the composite coating, simplify the preparation process, and reduce costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118772740B_ABST
    Figure CN118772740B_ABST
Patent Text Reader

Abstract

The present invention discloses a high barrier and strong corrosion resistant composite coating and its preparation method and application, belonging to the technical field of anti-corrosion coating. The preparation method of the present invention comprises the following steps: dispersing MXene powder and tannic acid in a solvent at a mass ratio of 1 to 5:1, and ultrasonically treating at room temperature for 30 to 60 minutes; obtaining MXene nanosheets loaded with tannic acid by centrifugation, washing and drying; and spraying the MXene nanosheets loaded with tannic acid and polymer resin evenly onto the surface of a metal substrate, and curing to obtain the coating. The preparation method of the present invention is simple and has low raw material cost. At the same time, a high barrier and strong corrosion resistant composite coating is constructed by a simple spraying method. The composite coating has a long service life, is easy to apply on a large scale, and has broad market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of anti-corrosion coatings, and in particular to a high-barrier and highly corrosion-resistant composite coating, and a preparation method and application thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As offshore equipment develops towards the deep sea, its service environment becomes more severe. Corrosion is a key factor affecting the service life of offshore metal parts, and it can cause huge economic losses and even threaten life safety. Polymer coatings play an important role in corrosion protection due to their wide applicability, low cost and ease of application. However, traditional polymer-based protective coatings can only provide passive barrier protection for metal substrates by forming an isolation layer. During the formation and use of the coating, micropores or microcracks will inevitably occur, causing interfacial corrosion, destroying the adhesion of the coating, and even causing the coating system to fail completely. Therefore, it is necessary to design and develop new composite coatings with both high barrier properties and strong corrosion resistance.

[0004] The study found that MXene two-dimensional nanosheets can play an efficient physical barrier role in the coating, preventing the rapid invasion of corrosive media and improving the corrosion resistance of nanocomposite coatings on carbon steel surfaces. However, MXene nanosheets will gradually degrade when exposed to humid air or water, and the layered structure of MXene nanosheets will be completely destroyed by oxidation as the corrosive media invade, and the natural re-stacking trend of MXene nanosheets in the polymer matrix is ​​still a problem that needs to be solved.

[0005] The patent with publication number CN114854237A discloses a method for inhibiting the oxidation of MXene nanomaterials and its application in anti-corrosion coatings. It uses graphene-based nanomaterials to hybridize and coat MXene nanomaterials, which are then modified by silane coupling agents. The prepared graphene-based / MXene nanohybrid materials are then added to a polymer matrix for metal corrosion protection. However, the preparation process of this patent involves two-step heat treatment, which is relatively complicated, and the price of graphene is relatively expensive, resulting in high coating costs. In addition, the modified MXene nanosheets in this patent do not achieve directional arrangement, making it difficult to give full play to the anti-corrosion properties of MXene.

[0006] Therefore, how to achieve the directional arrangement of MXene and improve its antioxidant properties through a simple and low-cost method, thereby improving the long-term corrosion resistance of the composite coating, is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of this, the present invention provides a high-barrier and highly corrosion-resistant composite coating and a preparation method and application thereof, which solve the problem of short service life of MXene-containing polymer coatings in harsh environments, and the preparation method is simple and low-cost.

[0008] In a first aspect, the present invention provides a method for preparing a high-barrier and highly corrosion-resistant composite coating, comprising the following steps:

[0009] Dispersing MXene powder and tannic acid in a solvent at a mass ratio of 1 to 5:1, and ultrasonically treating at room temperature for 30 to 60 minutes; obtaining MXene nanosheets loaded with tannic acid by centrifugation, washing and drying;

[0010] The MXene nanosheets loaded with tannic acid are evenly mixed with the polymer resin and then sprayed onto the surface of the metal substrate and cured to obtain the product.

[0011] Preferably, the solvent is selected from one or more of ethanol, methanol or water.

[0012] Preferably, the usage ratio of the MXene powder to the solvent is 1 g: 100-500 mL.

[0013] Preferably, the washing is washing with ethanol and water in sequence; and the drying is freeze-drying.

[0014] Preferably, the MXene powder is obtained by HF etching of Ti3AlC2 material.

[0015] Preferably, the mass ratio of the tannic acid-loaded MXene nanosheets to the polymer resin is 1:200-500.

[0016] Preferably, the polymer resin is selected from any one of epoxy resin, polyurea resin, acrylic resin and polyurethane resin.

[0017] Preferably, the curing step is: curing the sprayed metal substrate at room temperature for 1 to 3 hours, and then curing at 50 to 80° C. for 24 to 36 hours.

[0018] In a second aspect, the present invention provides a high-barrier and highly corrosion-resistant composite coating prepared by the above-mentioned preparation method.

[0019] In a third aspect, the present invention provides the application of the above-mentioned high-barrier and highly corrosion-resistant composite coating in metal corrosion protection.

[0020] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0021] (1) The present invention introduces tannic acid to modify MXene nanosheets, which can play a connecting role between MXene nanosheets, thereby achieving directional parallel arrangement of MXene nanosheets, preventing the accumulation of MXene nanosheets, and making the MXene nanosheets play an anti-corrosion role to the greatest extent; at the same time, the strong interaction between tannic acid and MXene nanosheets prevents the oxidative degradation reaction of MXene nanosheets, thereby greatly extending the service life of the composite coating;

[0022] (2) The preparation method of the present invention is simple, the reaction time is short and the raw material cost is low. At the same time, a high-barrier and strong corrosion-resistant composite coating is constructed by a simple spraying method. It has a wide range of applications, is easy to apply on a large scale, and has broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 is a scanning electron microscope image of the nanosheet loaded with tannic acid in Example 1 of the present invention;

[0025] Figure 2 The Bode diagrams and Nyquist diagrams of different coatings of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention exposed to different immersion times (3, 10, 25 and 50 days) in a 3.5wt% NaCl solution; wherein a is the Bode diagram amplitude-frequency characteristic curve of Comparative Example 1, a1 is the Bode diagram phase-frequency characteristic curve of Comparative Example 1, a2 is the Nyquist diagram of Comparative Example 1, b is the Bode diagram amplitude-frequency characteristic curve of Comparative Example 2, b1 is the Bode diagram phase-frequency characteristic curve of Comparative Example 2, b2 is the Nyquist diagram of Comparative Example 2, c is the Bode diagram amplitude-frequency characteristic curve of Example 1, c1 is the Bode diagram phase-frequency characteristic curve of Example 1, and c2 is the Nyquist diagram of Example 1;

[0026] Figure 3 It is a schematic diagram of the anti-corrosion mechanism of the high-barrier and highly corrosion-resistant composite coating of Examples 1 to 3 of the present invention. DETAILED DESCRIPTION

[0027] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0028] The present invention provides a method for preparing a high-barrier and highly corrosion-resistant composite coating, comprising the following steps:

[0029] Dispersing MXene powder and tannic acid in a solvent at a mass ratio of 1 to 5:1, and ultrasonically treating at room temperature for 30 to 60 minutes; obtaining MXene nanosheets loaded with tannic acid by centrifugation, washing and drying;

[0030] The MXene nanosheets loaded with tannic acid are evenly mixed with the polymer resin and then sprayed onto the surface of the metal substrate and cured to obtain the product.

[0031] The present invention ultrasonically treats tannic acid and MXene in a solvent for 30 to 60 minutes. The surface of the MXene nanosheet contains functional groups such as OH and F, which can generate hydrogen bonds with the OH functional groups of tannic acid, thereby realizing rapid loading under ultrasonic conditions and a short reaction time. Then, the MXene nanosheet loaded with tannic acid obtained by centrifugation, washing and drying has a good directional arrangement morphology, and the MXene nanosheets are distributed in parallel. The MXene nanosheets perpendicular to the coating thickness direction provide a winding diffusion path for the corrosive medium, which can delay corrosion. Tannic acid forms pillars between the MXene nanosheets to prevent the self-stacking of the MXene nanosheets, which can fully exert the role of MXene and make the modified nanosheets uniformly dispersed in the polymer resin. At the same time, the combination of tannic acid and MXene nanosheets can greatly reduce the oxidation degradation sites of MXene, and tannic acid can also act as a corrosion inhibitor to hinder the further penetration of corrosion, thereby greatly extending the service life of the final composite coating.

[0032] The solvent used for dispersion in the present invention can be selected from one or more of ethanol, methanol or deionized water to ensure that tannic acid is inserted between MXene nanosheets to orient the nanosheets.

[0033] In the present invention, the dosage ratio of MXene powder to solvent is 1 g: 100-500 mL, and this ratio is to ensure that MXene is fully dispersed, which is conducive to its directional arrangement under the action of tannic acid.

[0034] In the present invention, the washing is washing with ethanol and water in sequence, and the drying is freeze drying. Freeze drying can further ensure the integrity and fluffiness of the structure and is not easy to collapse.

[0035] In the present invention, the MXene powder is obtained by HF etching of Ti3AlC2 material. The present invention does not impose any special restrictions on the etching process, and the commonly used methods in the art can be used. Preferably, the preparation process of the MXene powder of the present invention is as follows: Ti3AlC2 material is added to HF etching solution, and then reacted at room temperature for 12 to 24 hours, the reaction product is washed with deionized water, and centrifuged several times until the pH value of the supernatant is not less than 6; then vacuum-assisted filtration is performed with a PVDF microporous membrane, and re-washed with deionized water; finally, freeze-dried under vacuum for 24 to 48 hours to obtain pure MXene powder.

[0036] In the present invention, the mass ratio of the tannic acid-loaded MXene nanosheets to the polymer resin is 1:200 to 500. Within the above mass ratio range, the anticorrosive effect of the tannic acid-loaded MXene nanosheets can be fully exerted. If the amount of the tannic acid-loaded MXene nanosheets added is too large, the performance improvement is not obvious, and the compatibility with the polymer matrix may be reduced.

[0037] The present invention does not impose any particular limitation on the type of polymer resin, and any polymer resin commonly used in the art may be used. For example, the polymer resin is selected from any one of epoxy resin, polyurea resin, acrylic resin and polyurethane resin.

[0038] The present invention does not impose any special restrictions on the spraying process, and the spraying method commonly used in the art can be used. Preferably, the present invention uses a spray gun with an air pressure of 30 to 50 kPa to spray onto the surface of the metal substrate at a distance of 15 to 20 cm.

[0039] The curing step of the present invention is: curing the sprayed metal substrate at room temperature for 1 to 3 hours, and then curing at 50 to 80° C. for 24 to 36 hours.

[0040] The present invention also provides a high-barrier and highly corrosion-resistant composite coating prepared by the above-mentioned preparation method, and the composite coating can be used for corrosion protection in harsh service environments.

[0041] The present invention also provides the use of the above-mentioned high-barrier and strong corrosion-resistant composite coating in metal corrosion protection, which is particularly suitable for the corrosion protection of marine metal parts.

[0042] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0043] In the following examples, the preparation process of MXene powder is as follows: 1.5g Ti3AlC2 powder is slowly added to 30mL HF etching solution under magnetic stirring conditions (within 10min), and reacted at room temperature (25±1°C) for 12h. The reaction product is washed with deionized water and centrifuged several times at 3500rpm until the pH value of the supernatant is not less than 6. The above-mentioned sediment is vacuum-assisted filtered with a polyvinylidene fluoride (PVDF) membrane with a pore size of 0.22μm, the sediment is re-washed with deionized water, and the sediment is freeze-dried under vacuum for 24h to obtain pure MXene powder.

[0044] Example 1

[0045] This embodiment provides a method for preparing a high-barrier and highly corrosion-resistant composite coating.

[0046] S1. Add 0.5 g of MXene powder into 200 mL of anhydrous ethanol and fully disperse it in an ultrasonic cleaner.

[0047] S2. Add 0.25 g of tannic acid powder to the above solution, ultrasonicate for 30 min at room temperature, and collect the tannic acid-loaded MXene nanosheets by centrifugation, washing with anhydrous ethanol and water, and freeze-drying.

[0048] S3. Mix the tannic acid-loaded MXene nanosheets and epoxy resin E51 in a mass ratio of 1:500, and spray the mixture onto the surface of the Q235 steel material at a distance of 15 cm using a spray gun with an air pressure of 50 kPa.

[0049] S4, the sprayed metal substrate was cured at room temperature for 3 h, and then cured in a 50 ° C oven for 36 h to obtain a high barrier and strong corrosion resistant composite coating, which was recorded as Ti3C2T x MXene@TA / EP coating.

[0050] Figure 1 This is a scanning electron microscope image of the nanosheet loaded with tannic acid in Example 1. It can be seen that tannic acid is loaded between the MXene nanosheet layers in the form of pillars.

[0051] Example 2

[0052] This embodiment provides a method for preparing a high-barrier and highly corrosion-resistant composite coating.

[0053] S1. Add 1 g of MXene powder into 200 mL of anhydrous ethanol and fully disperse it in an ultrasonic cleaner.

[0054] S2. Add 0.5 g of tannic acid powder to the above solution, ultrasonicate for 30 min at room temperature, and collect the tannic acid-loaded MXene nanosheets by centrifugation, washing with anhydrous ethanol and water, and freeze-drying.

[0055] S3. Mix the tannic acid-loaded MXene nanosheets and epoxy resin E51 in a mass ratio of 1:200, and spray the mixture onto the surface of the Q235 steel material at a distance of 20 cm using a spray gun with an air pressure of 40 kPa.

[0056] S4, the sprayed metal substrate was cured at room temperature for 1 hour, and then cured in an oven at 80°C for 24 hours to obtain a high barrier and corrosion resistant composite coating, which was recorded as Ti3C2T x MXene@TA / EP coating.

[0057] Example 3

[0058] This embodiment provides a method for preparing a high-barrier and highly corrosion-resistant composite coating.

[0059] S1. Add 2 g of MXene powder into 200 mL of anhydrous ethanol and fully disperse it in an ultrasonic cleaner.

[0060] S2. 0.4 g of tannic acid powder was added to the above solution, and ultrasonic treatment was performed at room temperature for 60 min. The MXene nanosheets loaded with tannic acid were collected by centrifugation, washing with anhydrous ethanol and water, and freeze drying.

[0061] S3. Mix the tannic acid-loaded MXene nanosheets and epoxy resin E51 in a mass ratio of 1:300, and spray the mixture onto the surface of the Q235 steel material at a distance of 15 cm using a spray gun with an air pressure of 30 kPa.

[0062] S4, the sprayed metal substrate was cured at room temperature for 2 h, and then cured in a 60 ° C oven for 36 h to obtain a high barrier and corrosion resistant composite coating, which was recorded as Ti3C2T x MXene@TA / EP coating.

[0063] Comparative Example 1

[0064] Compared with Example 1, this comparative example does not use MXene nanosheets loaded with tannic acid.

[0065] S1. Spray epoxy resin E51 onto the surface of Q235 steel material with a spray gun at an air pressure of 50 kPa at a distance of 15 cm.

[0066] S2. The sprayed metal substrate was cured at room temperature for 3 h, and then cured in an oven at 50° C. for 36 h to obtain a polymer coating, which was recorded as a pure EP coating.

[0067] Comparative Example 2

[0068] Compared with Example 1, this comparative example does not use tannic acid to modify MXene.

[0069] S1. Mix MXene powder and epoxy resin E51 in a mass ratio of 1:500, and spray the mixture onto the surface of Q235 steel material at a distance of 15 cm using a spray gun with an air pressure of 50 kPa.

[0070] S2, the sprayed metal substrate was cured at room temperature for 3 h, and then cured in an oven at 50 °C for 36 h to obtain a composite coating, which was recorded as Ti3C2T x MXene / EP coating.

[0071] Test example

[0072] The barrier and corrosion resistance properties of the coatings of Example 1, Comparative Example 1 and Comparative Example 2 in 3.5 wt % NaCl solution were evaluated by electrochemical impedance spectroscopy (EIS) measurement. Figure 2 The Bode and Nyquist plots of different coatings exposed to different immersion times (3, 10, 25, and 50 days) in 3.5 wt% NaCl solution are shown. In the initial stage of immersion, all coatings were intact, showing excellent protection. x Impedance (Z f=0.01Hz ) value is 6.36×10 9 Ω·cm 2 Ti3C2T of Example 1 x Impedance (Z f=0.01Hz ) value is 1.03×10 10 Ωcm 2 , compared with the pure EP coating of Example 1 (2.06×10 9 Ωcm 2 ) is one order of magnitude higher. At the end of the immersion phase, the Ti3C2T x Z of MXene@TA / EP f=0.01H 4.38×10 9 Ωcm 2 , almost EP(1.26×10 8 Ωcm 2 ). Z of all coatings f=0.01Hz The value dropped significantly after 25 days of immersion, which means that the electrolyte has penetrated through the coating. x Barrier effect of MXene@TA nanosheets, Ti3C2T in Example 1 xMXene@TA / EP coatings showed better performance than pure EP and Ti3C2T during the entire immersion period. x The larger impedance modulus value of MXene / EP indicates its best corrosion resistance.

[0073] The coatings of Examples 1 to 3 and Comparative Examples 1 to 2 were placed in a neutral salt spray test chamber for testing. The test results are shown in Table 1.

[0074] Table 1 Anticorrosion test results

[0075] Example / Comparative Example 15 days 30 days 60 days Example 1 No pitting No pitting No pitting Example 2 No pitting No pitting No pitting Example 3 No pitting No pitting No pitting Comparative Example 1 No pitting Micro pitting Extensive pitting Comparative Example 2 No pitting No pitting Micro pitting

[0076] After 15 days of testing, black pitting appeared under the pure EP coating of Comparative Example 1. As the exposure time was extended to 60 days, the number of pitting pits increased significantly, and the diameter of the pitting pits increased significantly, indicating that the electrolyte quickly invaded the steel / coating interface and localized corrosion occurred in the pure EP coating. This is attributed to the poor barrier properties of pure EP, which allows the corrosive ions to diffuse easily, eventually leading to coating failure. Ti3C2T x The introduction of MXene nanosheets significantly inhibited the generation of corrosion products, as shown in Table 1. However, even after 15 days, the Ti3C2T x A small amount of white spots appeared in the MXene / EP coating, indicating that some of the solution had penetrated into the coating. x The coatings of MXene@TA nanosheets (Examples 1 to 3) did not show any local corrosion during the entire test process. x The excellent anti-corrosion performance of the MXene / EP composite coating is attributed to the directional arrangement of MXene two-dimensional nanosheets in the coating and its high long-term stability, which inhibits the expansion of corrosion and significantly improves the environmental adaptability of the composite coating.

[0077] Ti3C2T of Examples 1 to 3 x The working principle of MXene / EP composite coating is as follows Figure 3 As shown in the figure, MXene nanosheets provide a tortuous diffusion path for the corrosive medium and delay corrosion; tannic acid acts as a pillar between MXene sheets, making the MXene two-dimensional nanosheets arranged in parallel in the resin and improving its dispersibility in the resin; at the same time, the combination of tannic acid and MXene blocks the reaction sites of MXene with oxygen and water, slowing down the oxidative degradation of MXene, and TA can also act as a corrosion inhibitor to prevent further corrosion, thereby achieving long-term corrosion resistance and environmental adaptability of the composite coating.

[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-barrier and highly corrosion-resistant composite coating, characterized in that: The steps include: Dispersing MXene powder and tannic acid in a solvent at a mass ratio of 1 to 5:1, and ultrasonically treating at room temperature for 30 to 60 minutes; obtaining MXene nanosheets loaded with tannic acid by centrifugation, washing and drying; The MXene nanosheets loaded with tannic acid are uniformly mixed with the polymer resin and then sprayed onto the surface of the metal substrate and cured to obtain the product; The solvent is selected from one or more of ethanol, methanol or water; the dosage ratio of the MXene powder to the solvent is 1g:100-500mL; the washing is washing with ethanol and water in sequence; the drying is freeze-drying; the mass ratio of the tannic acid-loaded MXene nanosheets to the polymer resin is 1:

500.

2. The preparation method according to claim 1, characterized in that The MXene powder is obtained by HF etching of Ti3AlC2 material.

3. The preparation method according to claim 1, characterized in that: The polymer resin is selected from any one of epoxy resin, polyurea resin, acrylic resin and polyurethane resin.

4. The preparation method according to claim 1, characterized in that: The curing step is: curing the sprayed metal substrate at room temperature for 1 to 3 hours, and then curing at 50 to 80° C. for 24 to 36 hours.

5. A high barrier and corrosion resistant composite coating prepared by the preparation method according to any one of claims 1 to 4.

6. Application of the high barrier and strong corrosion resistant composite coating as claimed in claim 5 in metal corrosion protection.

Citation Information

Patent Citations

  • Method for inhibiting oxidation of MXene nano material and application of MXene nano material in anticorrosive paint

    CN114854237A